A COGNITIVE THEORY DRIVEN NEW ORIENTATION OF INDONESIAN LESSONS - Edyta Nowinska (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
The main focus of this design research was on students’ mathematical thinking and skills and on their understanding of mathematical concepts and methods. The mathematical content our project starts with is the introduction of integers. For this content new learning environments have been developed, implemented and evaluated. An important question for the design of teaching and learning activities is how to establish appropriate models of mathematical concepts and methods for students and how they operate in students’ minds. In the lecture the use of those methodological concepts and theories in our approach will be explained and justified. The results indicate that the means and methods used in our project have a positive influence on the quality of teaching and learning processes in the class and on students’ mathematical thinking and skills.Keywords: Cognitive Theory, Indonesian Lessons, Mathematical Concept DOI: http://dx.doi.org/10.22342/jme.5.2.1501.170-190